Exploring Psilocybe spp. mycelium and fruiting body chemistry for potential therapeutic compounds - Waldbillig, Adam; Baranova, Maria; Neumann, Sarah; Andrade, Jonathan; Sidhu, Sharan (Frontiers in Fungal Biology, 2023)
Psilocybe mushrooms, otherwise known as "magic" mushrooms owe their psychedelic effect to psilocin, a 5HT 2A receptor agonist and metabolite of psilocybin, the primary indole alkaloid found in Psilocybe species. Metabolomics is an advanced fingerprinting tool that can be utilized to identify differences between fungal life stages, that may otherwise be unaccounted for. Here, by using targeted and untargeted (metabolomic) multivariate analysis, we demonstrate that Psilocybe chemical composition differs between mycelia, grain mycelia and fruiting bodies. Preferential accumulation of psilocybin, baeocystin, tryptophan, ergothioneine and phenylethylamine in fruiting bodies differentiated them from mycelia, however, α-GPC, N-Acetylglucosamine and Trimethylglycine were found to be proportionally higher in mycelia than fruiting bodies based on pareto scaled data. Considering the wealth of compounds with therapeutic potential that have been isolated from various fungal genera, it would be pertinent to study the compounds found in Psilocybe mycelia as potential naturally derived therapeutic targets.